2019
DOI: 10.1136/bmjopen-2018-024207
|View full text |Cite
|
Sign up to set email alerts
|

Geographical inequalities in acute myocardial infarction beyond neighbourhood-level and individual-level sociodemographic characteristics: a Danish 10-year nationwide population-based cohort study

Abstract: ObjectiveThis study examined whether geographical patterns in incident acute myocardial infarction (AMI) were explained by neighbourhood-level and individual-level sociodemographic characteristics.DesignAn open cohort study design of AMI-free adults (age ≥30 years) with a residential location in Denmark in 2005–2014 was used based on nationwide administrative population and health register data linked by the unique personal identification number. Poisson regression of AMI incidence rates (IRs) with a geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 26 publications
(26 reference statements)
1
27
0
Order By: Relevance
“…The median parish population size in Denmark in 2014 was 1038 (range 25-43,052) and the median parish area was 16.2 km 2 (range 0.1-114.8 km 2 ). 2 Kjaerulff et al 1 reported weak correlations between parish-level and individual-level sociodemographic variables. 2 Such correlations would be stronger if the parishes were replaced by smaller neighbourhoods that were more homogenous with regard to social deprivation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The median parish population size in Denmark in 2014 was 1038 (range 25-43,052) and the median parish area was 16.2 km 2 (range 0.1-114.8 km 2 ). 2 Kjaerulff et al 1 reported weak correlations between parish-level and individual-level sociodemographic variables. 2 Such correlations would be stronger if the parishes were replaced by smaller neighbourhoods that were more homogenous with regard to social deprivation.…”
mentioning
confidence: 99%
“…They have previously published an analogous study on the incidence of AMI in the same setting. 2 We acknowledge that studies of geographical inequalities in cardiovascular disease (CVD) incidence and survival are challenging. Nevertheless, such studies can help to target areas with a heavy CVD burden and/ or an unfavourable mortality rate among incident cases, which, in turn, may enable the rational allocation of prevention resources.…”
mentioning
confidence: 99%
See 3 more Smart Citations